TMEM59 defines a novel ATG16L1-binding motif that promotes local activation of LC3 - Boada-Romero, Emilio (European Molecular Biology Organization, 2013)
Selective autophagy underlies many of the important physiological roles that autophagy plays in multicellular organisms, but the mechanisms involved in cargo selection are poorly understood. Here we describe a molecular mechanism that can target conventional endosomes for autophagic degradation. We show that the human transmembrane protein TMEM59 contains a minimal 19-amino-acid peptide in its intracellular domain that promotes LC3 labelling and lysosomal targeting of its own endosomal compartment. Interestingly, this peptide defines a novel protein motif that mediates interaction with the WD-repeat domain of ATG16L1, thus providing a mechanistic basis for the activity. The motif is represented with the same ATG16L1-binding ability in other molecules, suggesting a more general relevance. We propose that this motif may play an important role in targeting specific membranous compartments for autophagic degradation, and therefore it may facilitate the search for adaptor proteins that promote selective autophagy by engaging ATG16L1. Endogenous TMEM59 interacts with ATG16L1 and mediates autophagy in response to Staphylococcus aureus infection.